Enzymatic lipase-based methyl esterified Citrullus colocynthis L. biodiesel for improved combustion, performance and emission characteristics. (1st January 2022) - Sheng, Yequan; Brindhadevi, Kathirvel; Eed, Emad M.; Xia, Changlei; Chi, Nguyen Thuy Lan
Graphical abstract: Highlights: Enzymatic lipase-based methyl esterified Citrullus colocynthis L . were examined in the diesel engine. 10% to 30% blends were tested by varying the engine speeds. 30% Citrullus colocynthis L . reduced the BTE owing to the viscosity. Significant reduction in pollutant emissions were observed at different engine speeds. Abstract: The recent advancement of finding an alternative to fossil fuel was attempted on the seeds of Citrullus colocynthis L. for producing biofuel. The oil source for biofuel was taken to do the detailed study and experimental work. From the experimental work, the most important characteristics, which are necessary to identify the performance and combustion, the quality of the fuel used in an engine. The engine taken for the fuel study was a single cylinder, four stroke, water cooled DI engine. All tests were conducted at different engine speeds as 1800 rpm, 2000 rpm, 2200 rpm. 2400 rpm and 2800 rpm. The Brake Thermal Efficiency (BTE), Brake Specific Fuel Consumption (BSFC), and Brake Power (BP) reflects the combustion status within the engine and the emission CO, CO2, NOX, and HC gives the emission tendency of the fuel used that has to be reduced. The naturally plentiful plant of citrullus coloncynthis L. seeds were used for the biodiesel production. Four different fuel combinations were tried in the engine as D100 (Pure diesel), CC10 ( Citrullus coloncynthis biofuel 10% + Diesel 90%), CC20 ( Citrullus coloncynthis biofuel 20% + Diesel 80%) and CC30 ( Citrullus coloncynthis biofuel 30% + Diesel 70%). From the results, it is evident that the use of CC Biofuel with 10% provides little lower value of BTE and BP and slightly higher BSFC than the pure diesel results. Considering the emission nature, it highly reduced the emission of CO and HC except NOX and CO2 .